ISLAM LIBERAL BUDHY MUNAWAR RACHMAN (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2021)
Islamic thought in Indonesia will never end, Islam is always interesting to observe, one of which is about the birth of liberal Islamic thought in the 1970s. This started when Cak Nur gave a speech at the Eid al-Fitr gathering organized by HMI, PII, GPI and Persami. In his speech he said that Islamic thought is currently in a state of confusion, because there are many Islamic parties who want to revive an Islamic state. Therefore, Cak Nur proposed a controversial cargon, namely "Islam Yes, Islamic Party No!". The cargo became a controversy that caused divisions among Islamic intellectuals. This research is a literature study, namely research that cites books as the source, using books on Islam and Liberalism as the primary data, then secondary data is obtained through data that is related to the theme. The technique used in this research is descriptive analysis method. By analyzing primary data and secondary data, then a selection process is carried out that can find results that are in accordance with this research. The results of this research analysis are, First, liberal Islam according to Budhy Munawar Rachman includes two things, namely: the basis and nature of liberal Islam. This explains that all humans have the freedom to choose their beliefs. The two ethical principles can be a solution in answering the problems that will occur in Islam. The three principles of this method aim to develop liberal Islamic thought so that it can be a solution and provide a new discourse that maintains existing Islamic knowledge.